Wyoming matchmaker - Senate, Melissa (Senate, Melissa. Dawson family ranch., 2021)
Bear Ridge, Wyoming real estate agent Danica Dunbar decides to combine selling property with dating services, but when she can't stop thinking about her first bachelor candidate, police detective Ford Dawson, Danica begins to think maybe she's found her match.